2019
DOI: 10.1016/j.drugpo.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex behaviours among men who have sex with men: A systematic review of the literature

Abstract: Background: 'Chemsex' is the use of drugs before or during planned sexual events to facilitate, enhance, prolong and sustain the experience. Drugs associated with chemsex are methamphetamine, GHB/GBL, mephedrone, cocaine and ketamine. This review syntheses published research on the antecedents, behaviours and consequences associated with chemsex behaviours among men who have sex with men (MSM). Methods: Papers from high income countries which were published between January 2000 and September 2018 reporting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
331
8
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(388 citation statements)
references
References 47 publications
26
331
8
23
Order By: Relevance
“…18 These parties are becoming very popular in gay culture because it facilitates the interaction with other MSM and often lowers inhibition for esoteric sex (eg, fisting) that can increase the risk for HIV and other STIs. 18 In a cross-sectional study among 388 MSM in San Francisco in 2001, 15% used meth before or during their most recent unprotected insertive anal sex encounter. 16 Men who use meth during sexual activities have more sexual partners with whom they engage in unprotected anal sex as the receptive partner as well as higher frequency of unprotected oral sex.…”
Section: Meth Use and Sexual Risk Behaviors For Hiv Among Men Who Havmentioning
confidence: 99%
See 1 more Smart Citation
“…18 These parties are becoming very popular in gay culture because it facilitates the interaction with other MSM and often lowers inhibition for esoteric sex (eg, fisting) that can increase the risk for HIV and other STIs. 18 In a cross-sectional study among 388 MSM in San Francisco in 2001, 15% used meth before or during their most recent unprotected insertive anal sex encounter. 16 Men who use meth during sexual activities have more sexual partners with whom they engage in unprotected anal sex as the receptive partner as well as higher frequency of unprotected oral sex.…”
Section: Meth Use and Sexual Risk Behaviors For Hiv Among Men Who Havmentioning
confidence: 99%
“…MSM who report having four or more male sex partners are 1.58 (95% CI: 1.06, 2.36) times more likely to contract HIV in comparison with MSM who reported fewer partners . A recent systematic review found that chem sex parties (also known as party and play or PnP) are popular events where meth and other drugs are used and abused . These parties are becoming very popular in gay culture because it facilitates the interaction with other MSM and often lowers inhibition for esoteric sex (eg, fisting) that can increase the risk for HIV and other STIs .…”
Section: Introductionmentioning
confidence: 99%
“…The rates were slightly lower in Asia, ranged from 28% in mainland China, 18% in Thailand, 14% in Vietnam, to 7% in Malaysia (14). Worldwide, the prevalence of chemsex ranged from 3% to 35% among GBMSM (7,13,15). A recent study reported that 12% of GBMSM in Hong Kong had SDU in the past six months (excluding the use of amyl nitrite alone) (16).…”
mentioning
confidence: 99%
“…In line with numerous published studies, psychoactive substances were defined as the following: 1) ketamine, 2) methamphetamine, 3) cocaine, 4) cannabis, 5) ecstasy, 6) Dormicum/Halcion/Erimin 5/non-prescription hypnotic drugs, 7) heroin, 8) cough suppressant (not for curing cough), 9) amyl nitrite (popper), 10) GHB/GBL (γ-hydroxybutyrate), 11) 5-methoxy-N, Ndiisopropyltryptamine (Foxy), and 12) mephedrone (5)(6)(7). Sexualized drug use (SDU) refers to the use of any of the abovementioned psychoactive substances before/during sexual intercourse (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation